In vitro evaluation of anticancer effect on momordica balsamina linn. leaf extract in human MCF-7 cancer cells - Boshielo, Itumeleng Tania (My University, 2017)
Cancer is a broad group of various diseases characterised by unregulated cell proliferation which leads to the formation of tumours (Vickers, 2004). Some tumours remain confined to their site of origin while some gain the ability to spread to other parts of the body, a process known as metastasis (Weiss, 1990). The burden of cancer continues to rise, due to inefficient prevention strategies and serious side effects, as well as the cost of cancer regimens (Sondhi et al., 2010). Medicinal plants represent a reservoir of bioactive compounds that can be useful in the management of cancer with less or no side effects (Wong et al., 2012). The aim of this study was to investigate the anti-cancer effects of M. balsamina leaf extract in breast MCF-7 cancer cells. In this study, M. balsamina leaves powder was extracted using acetone. The biological effect of the extract was assessed on the viability of MCF-7 cells using the MTT assay. The extract’s ability to induce apoptosis was assessed using the Hoechst/propidium iodide dual staining method. Its anti-metastatic potential was investigated by determining its effect on MCF-7 cell migration, attachment and invasion using wound healing, adhesion, invasion assay, respectively. The human apoptosis antibody and human angiogenesis antibody array kits were used to determine the effect of the extract on the expression levels of proteins involved in apoptosis and metastasis, respectively. Treatment of MCF-7 cells with different concentrations of the extract showed a significant decrease in cell viability after 48 h incubation at 10 - 20 µg/ml. The decrease in cell viability was associated with the induction of apoptosis as seen by nuclear condensation and loss of membrane permeability in cells treated with the extract. Inhibition of migration, adhesion and invasiveness of the MCF-7 cells was seen in the treated cells. The extract also modulated proteins implicated in cell apoptosis, adhesion, migration and invasion such as Bcl-2 family of proteins, IGFBP, uPA, MMPs. In conclusion, based on the results, the extract show pro-apoptotic and anti-metastasis potential. Thus M. balsamina can be considered as a potential source of compounds with anti-cancer activity
Thesis (M.Sc. (Biochemistry)) --University of Limpopo, 2017
Keywords: M. balsamina; MCF-7 cancer cells; Medicinal plants; Momordica; Cucurbitaceae; Medicinal plants; Cancer cells